Cleaner production of rubber seed oil methyl ester using a hydrodynamic cavitation: optimisation and parametric study - Bokhari, A. (Elsevier Ltd, 2016)
Producing sustainable biodiesel using non-edible feedstock via transesterification reaction assisted hydrodynamic cavitation technology is a viable way to offset fossil diesel usage. This technology has affirmative environmental impacts with lower energy consumption and the reaction time and offers a cleaner possibility. Methyl ester conversion has been observed at a different inlet pressure of 1â3.5 bar on different plate geometries in 50 L pilot hydrodynamic cavitation reactor. Orifice plate with 21 holes of 1 mm and inlet pressure of 3 bar found to be the optimal arrangement. Parametric optimisation used response surface methodology and found as alcohol to oil ratio of 6:1, catalyst loading of 1 wt., reaction time of 18 min and reaction temperature of 55 Â°C. About 5 fold shorter reaction time, 6.5 fold higher energy efficiency and 4.9 fold higher reaction rate constant using hydrodynamic cavitation compared to mechanical stirring. Hydrodynamic cavitation is concluded to be time saving and energy efficient process compared to mechanical stirring. This makes the process more environmental friendly using hydrodynamic cavitation. Most of the properties in rubber seed oil methyl ester were met the EN 14214 and ASTM D 6751 standards. Â© 2016 Elsevier Ltd